2003
DOI: 10.1249/01.mss.0000078938.84161.22
|View full text |Cite
|
Sign up to set email alerts
|

The Human Gene Map for Performance and Health-Related Fitness Phenotypes: The 2002 Update

Abstract: This review presents the 2002 update of the human gene map for physical performance and health-related phenotypes. It is based on peer-reviewed papers published by the end of 2002 and includes association studies with candidate genes, genome-wide scans with polymorphic markers, and single gene defects causing exercise intolerance to variable degrees. The genes and markers with evidence of association or linkage with a performance or fitness phenotype in sedentary or active people, in adaptation to acute exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 133 publications
0
42
0
1
Order By: Relevance
“…In an early study reported by Bouchard et al (31), substantial betweenindividual variance in adaptation to exercise was observed. Subsequent studies have reported inheritance of fitness phenotypes (32) and linkage between genomic regions and fitness phenotypes (33). In combination, these data provide compelling evidence that improvements in fitness may be more easily achieved in certain individuals than in others and that this difference relates to genetic or other nonmodifiable factors.…”
Section: Statistical Correction For Measurement Errormentioning
confidence: 94%
“…In an early study reported by Bouchard et al (31), substantial betweenindividual variance in adaptation to exercise was observed. Subsequent studies have reported inheritance of fitness phenotypes (32) and linkage between genomic regions and fitness phenotypes (33). In combination, these data provide compelling evidence that improvements in fitness may be more easily achieved in certain individuals than in others and that this difference relates to genetic or other nonmodifiable factors.…”
Section: Statistical Correction For Measurement Errormentioning
confidence: 94%
“…In addition, genes decide how sportsmen will respond to trainings and other environmental factors affecting their performance (30). For example, while a sportsman possessing genes that affect his durability negatively has potential to respond to durability trainings applied, he will be more successful than those having genes that affect this ability positively (49). Besides, genes' direct effect on hereditary characteristics is one of the important topics that genetic determinism concentrates on (43).…”
Section: Importance Of Talent Selection and Genetics In Sportmentioning
confidence: 99%
“…For example, while the genes have been associated with athletic performance provide sportsmen with the potential to respond trainings positively, same genes enable more effective function of metabolic process with exercise in sedentary individuals. However, while a series of genes provide capacity to maintain energy long time in durability sportsmen, they may lead to problems related to obesity, diabetes and cardiac diseases in sedentary individuals (49).…”
Section: Sportsman Health -Genetics Relationshipmentioning
confidence: 99%
“…The benefit of activity is partly mediated through the maintenance of strength and physical endurance [58], and trials of both strength and aerobic interventions have shown them to be beneficial in improving function in older adults [52,54]. However, despite the general benefit of exercise, individual responses to exercise vary [5].…”
Section: Introductionmentioning
confidence: 99%